2007
DOI: 10.1063/1.2745438
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous matrices for quantum computation with improved response through redundance

Abstract: We present a solid state implementation of quantum computation, which improves previously proposed optically driven schemes. Our proposal is based on vertical arrays of quantum dots embedded in a mesoporous material which can be fabricated with present technology. The redundant encoding typical of the chosen hardware protects the computation against gate errors and the effects of measurement induced noise. The system parameters required for quantum computation applications are calculated for II-VI and III-V ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…The results in table I suggest that for a long range interaction the HM, EHM and EHM+CH are not at all suitable to accurately model the average single-site entanglement of realisable quantum dots when d is compa-rable or larger than w. However they all appear to be a fair approximation to the average single-site entanglement in the limiting case of d = 0 and small U suggesting that the HM, EHM and EHM+CH are useful in modelling systems of dots when d is much smaller than w as such systems correspond to small U . Interestingly, this may include the case of a single dot when modelled as a (small) set of finite partitions (system GaAs (3) in table I).…”
Section: Comparison With Hubbard Model Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results in table I suggest that for a long range interaction the HM, EHM and EHM+CH are not at all suitable to accurately model the average single-site entanglement of realisable quantum dots when d is compa-rable or larger than w. However they all appear to be a fair approximation to the average single-site entanglement in the limiting case of d = 0 and small U suggesting that the HM, EHM and EHM+CH are useful in modelling systems of dots when d is much smaller than w as such systems correspond to small U . Interestingly, this may include the case of a single dot when modelled as a (small) set of finite partitions (system GaAs (3) in table I).…”
Section: Comparison With Hubbard Model Variantsmentioning
confidence: 99%
“…Here I: Estimate of the on-site interaction strength U for different QD systems: GaAs-type systems with reduced mass m ef f = 0.067me and dielectric constant ǫ = 10.9 (GaAs (1) to GaAs (3) ); GaAs-based system with m ef f = 0.067me and ǫ = 12.1 (GaAs (4) [24]); and CdSe-based system with m ef f = 0.45me and ǫ = 9.1 [25]. For the d = 0 limiting case, the system is physically a single dot of width 44nm but modelled as four partitions of width w = 11 nm.…”
Section: Particle-particle Spatial Entanglementmentioning
confidence: 99%
“…In this context quantum dots are thought of as a viable possibility in the quest to construct scalable quantum processors [2][3][4][5][6][7][8][9]. With this in mind, finding accurate ways to calculate the entanglement between electrons in quantum dots becomes important for quantum information processing.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important for CdSe/CdS-based systems. In this case, for a T iO 2 matrix with hexagonally packed pores, to be able to regard the QD stacks as independent, the matrix walls must be at least 4.5 nm thick and the probability of individual success as high as p = 0.9 [9]. However the use of matrices with pores aligned along 1D chains could allow the probability of success for isolated stacks to be as low as 0.76, with matrix walls as thin as 3 nm.…”
Section: Discussionmentioning
confidence: 99%
“…(2)). It was found [9] that for the GaN/AlN system with TiO 2 matrix, and matrix wall thicknesses of 6 nm, each stack could be considered isolated from the rest of the ensemble for all p. For a CdSe/CdS hardware it was found that for matrix walls 6 nm thick the stacks could be considered isolated for p > ∼ 0.86, and similarly for a wall thickness of 4.5 nm for p > ∼ 0.91. Figure 3 shows the ratio R = |∆E tot inter |/|∆E| against the number of shells of neighbours included in the calculation, for the GaN/AlN system in a TiO 2 matrix ( T iO 2 ≈ 100) [12] with 2 nm walls, and p = 0.83.…”
Section: Influence Of Materials Parameters and Dimensionalitymentioning
confidence: 96%